Implementasi Gerakan Literasi Sekolah Dalam Menanamkan Karakter Siswa SD Negeri Suryodiningratan 3 - Kurniawati, Wahyu; Silmi, Fina Idamatus; Rigianti, Henry Aditia; Novitasari, Rahma Kurnia; Trilisiana, Novi (Universitas Muhammadiyah Magelang, 2023)
This study aims to find out how the implementation of the School Literacy Movement (GLS) in instilling the character of SD Negeri Suryodiningratan 3 students. The background of this research is taken from students who have difficulty in solving problems that exist in the surrounding environment, such as counting when eating snacks in the canteen, and others. This study uses a descriptive qualitative type, data collection using interviews, observation, documentation. Data analysis using data reduction, and drawing conclusions. The results of this study state several findings, including: School Literacy Movement in instilling student character in SD Negeri Suryodiningratan 3. Obstacles encountered in implementing the School Literacy Movement in instilling student character in SD Negeri Suryodiningratan 3. Solutions to obstacles found in carrying out the School Literacy Movement activities in instilling student character at SD Negeri Suryadiningratan 3. The implementation of the School Literacy Movement has a very important role in education. With these literacy activities can make a good impact in the world of education. Increase knowledge, and information. As well as helping students in solving a problem that exists in the surrounding environment.